Metabolic Adaptation of Paracoccidioides brasiliensis in Response to in vitro Copper Deprivation - Petito, Guilherme; de Curcio, Juliana Santana; Pereira, Maristela; Bailão, Alexandre Melo; Paccez, Juliano Domiraci; Tristão, Gabriel Brum; de Morais, Camila Oliveira Barbosa; de Souza, Marcelo Valle; de Castro Moreira Santos, Agenor; Fontes, Wagner; Ricart, Carlos André Ornelas; de Almeida Soares, Célia Maria (Frontiers in Microbiology, 2020)
Copper is an essential micronutrient for the performance of important biochemical processes such as respiration detoxification, and uptake of metals like iron. Studies have shown that copper deprivation is a strategy used by the host against pathogenic fungi such as Cryptoccocus neoformans and Candida albicans during growth and development of infections in the lungs and kidneys. Although there are some studies, little is known about the impact of copper deprivation in members of the Paracoccidioides genus. Therefore, using isobaric tag labelling (iTRAQ)-Based proteomic approach and LC-MS/MS, we analyzed the impact of in vitro copper deprivation in the metabolism of Paracoccidioides brasiliensis. One hundred and sixty-four (164) differentially abundant proteins were identified when yeast cells were deprived of copper, which affected cellular respiration and detoxification processes. Changes in cellular metabolism such as increased beta oxidation and cell wall remodeling were described.